Empowering the Battle: Bioenhancers as Allies Against Cancer Drug Resistance - Jadhav, Pratiksha Vasant; Prasath, Naga Jothi; Gajbhiye, Saurabh G.; Rane, Utkarsha Arun; Agnihotri, Tejas Girish; Gomte, Shyam Sudhakar; Jain, Aakanchha (Current Pharmaceutical Biotechnology, 2024)
Background: Drug resistance has been a great hindrance in the path of counteracting diseases like cancer and is driven by drugs misuse and overuse. In terms of cancer, resistance has been developed due to cellular changes, altered growth activation pathways, increased expression of efflux proteins, and changes in the local physiology of cancer (blood supply, tissue hydrodynamics, increased mutation rate/epigenetics, tumor cell heterogeneity). One of the approaches to address these challenges is the use of bioenhancers, which can overcome drug resistance, thereby improving bioavailability (BA). Conclusion: Bioenhancers when combined with drugs can elicit pharmacological activity. They are generally combined with therapeutic agents at low doses, which increase the BA or therapeutic activity of active pharmaceutical ingredient (API). This review sheds light on the synthesis and classification of bio-enhancers. It also discusses different applications of bio-enhancers like piperine, ginger, quercetin, curcumin, etc. in the treatment of cancer. The review also presents some of the recent advancements in terms of nanocarriers for delivering API combined with bioenhancers.
Keywords: cancer